Coagulant agent for water treatment. - Zainal Abidin, Zurina; Yunus, Robiah (2011)

(untitled)
In this invention, a new type of biocoagulant agent suitable for wastewater treatment extracted from Jatropha seeds and presscake (residue after oil extraction) is described. The biocagulant agent is a protein and extracted from the seed and presscake through blending process. The Jatropha seeds is grounded into fine powder and dissolved in distilled water. The coagulant from the presscake is obtained by dissolving the Jatropha cake in distilled water. After filtration, the supernatant is added to wastewater sample. It was found that for kaolin wastewater, the turbidity removal more than 90%. The optimum blending time to extract the active agent is found to be 2 minutes while the optimum dosage and pH are 120mg/litre and pH 3 respectively.